I took the only path to see you : a guide to finding professional success without sacrificing personal happiness - Fisher, Jon B., 1972-; Fisher, Gerald A. (Gerald Allen); Wang, Wally (John Wiley & Sons, Inc., 2021)
"The thesis of I Took The Only Path To See You is that you can achieve success in any field you choose, but pursuing financial or professional success at the expense of your family or personal relationships is ultimately empty and hollow. Healthy families and good friendships pay sustained rewards that can never be measured in dollars. In the book, Fisher shares his experiences with friends who have risen to become number one in their fields, such as 49er Hall of Famer Ronnie Lott and billionaire Zoom CEO Eric Yuan. Despite the tremendous effort needed to achieve their outward success, neither Ronnie Lot nor Eric Yuan ever lost sight of the importance of being a good person. While not everyone may make it to the top of their chosen field, everyone can always work toward becoming a better person--for themselves, their families and friends, and the world at large. This personal growth is the key to real personal achievement and happiness as well as laying the foundation for stronger relationships between family members, friends, and even other races and nationalities."--